Personality Characteristics And Obesity - Asthana Sunita; Gupta V.M (Indian Journal of Community Medicine, 1999)
Research question: Whether certain personality characteristics of obese women make them prone towards psychological problem? Objective: To assess certain personality characteristics of obese women. Study design: Cross-sectional community based study. Setting: Affluent localities of Varanasi city. Participants: Women above 15 years of age. Statistical Analysis: Mean, S.D and â€˜tâ€ test. Results: On 16 PF scale obese women were found more reserved, critical, depressed, worried and troubled than the non-obese women. Obese also manifested subsequently less felling of contentment, happiness satisfaction with life experiences, low sense of achievement on PGI Well-Being. Obese women showed more distress and apprehension over their negative evaluation and distressed with day to day Conclusion: Obese women evidenced significantly more neurotic than non- obese women.